On the harmonic analysis of cup anemometer rotation speed: A principle to monitor performance and maintenance status of rotating meteorological sensors. (September 2015) - Pindado, Santiago; Cubas, Javier; Sorribes-Palmer, Félix
Graphical abstract: Highlights: Cup anemometer performance is related to the harmonic terms of the output signal. Rotational asymmetries of the rotor are reflected in the harmonic terms. An easy way to check rotating wind sensors status is proposed. 3-cup analytical model is accurate enough to study complex effects on cup anemometer. Abstract: The calibration results of one anemometer equipped with several rotors, varying their size, were analyzed. In each case, the 30-pulses pert turn output signal of the anemometer was studied using Fourier series decomposition and correlated with the anemometer factor (i.e., the anemometer transfer function). Also, a 3-cup analytical model was correlated to the data resulting from the wind tunnel measurements. Results indicate good correlation between the post-processed output signal and the working condition of the cup anemometer. This correlation was also reflected in the results from the proposed analytical model. With the present work the possibility of remotely checking cup anemometer status, indicating the presence of anomalies and, therefore, a decrease on the wind sensor reliability is revealed.